2020
DOI: 10.1002/advs.202001778
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Patterning of Carbon Nanotubes: Techniques, Applications, and Future

Abstract: Carbon nanotube (CNT) devices and electronics are achieving maturity and directly competing or surpassing devices that use conventional materials. CNTs have demonstrated ballistic conduction, minimal scaling effects, high current capacity, low power requirements, and excellent optical/photonic properties; making them the ideal candidate for a new material to replace conventional materials in next-generation electronic and photonic systems. CNTs also demonstrate high stability and flexibility, allowing them to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 633 publications
(838 reference statements)
0
57
0
Order By: Relevance
“…For example, it has been reported that Ag nanowire-based hybrid electrodes comprising Ag nanowires, carbon nanotube, and graphene oxide can achieve efficient wearable sensors [ 21 ] and organic photovoltaics [ 22 ]. In addition, the electrospray assisted etching of Ag nanowires was able to fabricate a quasi-periodic structure with the potential for various optoelectronic applications [ 23 ] and several patterning methods for Ag nanowires including subtractive methods, additive methods and printing methods were developed to achieve a precise patterning of Ag nanowire networks [ 24 , 25 ]. To this end, we recently adopted AgNWs as metal top electrodes and fabricated a transparent speaker that could be attached to a display [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that Ag nanowire-based hybrid electrodes comprising Ag nanowires, carbon nanotube, and graphene oxide can achieve efficient wearable sensors [ 21 ] and organic photovoltaics [ 22 ]. In addition, the electrospray assisted etching of Ag nanowires was able to fabricate a quasi-periodic structure with the potential for various optoelectronic applications [ 23 ] and several patterning methods for Ag nanowires including subtractive methods, additive methods and printing methods were developed to achieve a precise patterning of Ag nanowire networks [ 24 , 25 ]. To this end, we recently adopted AgNWs as metal top electrodes and fabricated a transparent speaker that could be attached to a display [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, every coin has two sides, the distinctive structures of CNTs increase their hydrophobicity in water and leave them with inherent cytotoxicity [ 29 ]. Therefore, elevating hydrophilicity and reducing cytotoxicity through functionalizing CNTs with different chemical groups or biomolecules are of great significance to improve their safety and effectiveness for broad application in cancer therapy [ 30 ]. Thus, this review highlights the update progress of CNTs as promising drug delivery vehicles in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the wettability can be done by controlling the chemistry of the substrate surface to make hydrophilic/hydrophobic patterns, and this has been researched extensively. [ 15–18 ] However, the wettability can also be controlled by the substrate surface topography. “Topographical” discontinuous dewetting (TDD) has been used to selectively fill patterned, open cavities with functional inks, depositing the functional materials into the open cavities in desired patterns.…”
Section: Introductionmentioning
confidence: 99%